2019
DOI: 10.1002/cre2.223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of swallowing function in patients with oropharyngeal secretions

Abstract: BackgroundSeveral studies have reported a strong association between the presence of oropharyngeal secretions in the laryngeal vestibule and the likelihood of aspiration of food or liquid. However, no previous studies have evaluated the accumulation of saliva and swallowing dynamics.ObjectiveThe objective of this study was to examine the factors related to decreased function that result in saliva accumulation based on images from videofluoroscopic examination of swallowing (VF) performed on the same day as vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…, decreased laryngeal sensation, incomplete pharyngeal constriction, and impaired upper esophageal sphincter opening). 27 , 28 Aspiration events could also be caused by swallowing impairment during the oral swallowing phase, such as bolus propulsion and premature spillage. However, compared with food/liquid swallowing, spontaneous swallowing that manage oropharyngeal secretions bypassed the participation of oral phase more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…, decreased laryngeal sensation, incomplete pharyngeal constriction, and impaired upper esophageal sphincter opening). 27 , 28 Aspiration events could also be caused by swallowing impairment during the oral swallowing phase, such as bolus propulsion and premature spillage. However, compared with food/liquid swallowing, spontaneous swallowing that manage oropharyngeal secretions bypassed the participation of oral phase more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher PR and MSS scores were also observed in the infratentorial stroke group, which further indicated the importance of infratentorial brain regions. The accumulation of saliva was reported to correlate with reduced laryngeal sensation, laryngeal displacement, and UES relaxation, all of which were modulated by the infratentorial brain regions (Borders et al., 2019 ; Brady et al., 2016 ; Yamaguchi et al., 2019 ). Furthermore, some anatomical reasons may also be important.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recently published intervention studies have assessed secretion severity as a primary or secondary outcome measure to determine responses to therapeutic interventions [26,28]; however, only one used a validated tool [28]. The SSRS [4] has been used in a number of articles evaluating patient cohorts, including diabetes [29], ALS [10] and referred dysphagic patients of mixed cause [30 ▪ ,31 ▪▪ ]. The NZSS (validated and published in 2018) [13 ▪▪ ] is being used more often now, perhaps due to its advantage of covering amount, location and response to secretions.…”
Section: Research Use Of Secretion Toolsmentioning
confidence: 99%
“…Yamaguchi et al . [30 ▪ ] provide us with more objective, physiological evidence to understand the pathophysiology underlying pooled secretions. Using same day nasendoscopy and videofluoroscopic swallow studies (VFSS) to evaluate both secretion status and swallow biomechanics, they reported that patients with elevated SSRS scores had reduced horizontal displacement of the hyoid bone, reduced laryngeal movement, reduced upper oesophageal sphincter (UES) opening and absence of base of tongue to posterior pharyngeal wall approximation compared with those with no accumulated secretions.…”
Section: Pathophysiology Associated With Accumulated Secretionsmentioning
confidence: 99%